2022
DOI: 10.1021/acs.molpharmaceut.2c00594
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features Affecting the Interactions and Transportability of LAT1-Targeted Phenylalanine Drug Conjugates

Abstract: L-type amino acid transporter 1 (LAT1) transfers essential amino acids across cell membranes. Owing to its predominant expression in the blood−brain barrier and tumor cells, LAT1 has been exploited for drug delivery and targeting to the central nervous system (CNS) and various cancers. Although the interactions of amino acids and their mimicking compounds with LAT1 have been extensively investigated, the specific structural features for an optimal drug scaffold have not yet been determined. Here, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This phenomenon mirrors our previous findings that bulky side chains can increase LAT1 affinity while reducing transport velocity 22 , 23 . Such a trend is also observed in the case of melphalan, an anticancer drug known for its high LAT1 affinity and low transport velocity, attributed to its bulky side chain 22 24 , 35 , 36 . These findings underscore the importance of considering both affinity and transport efficiency when developing LAT1-targeted compounds.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This phenomenon mirrors our previous findings that bulky side chains can increase LAT1 affinity while reducing transport velocity 22 , 23 . Such a trend is also observed in the case of melphalan, an anticancer drug known for its high LAT1 affinity and low transport velocity, attributed to its bulky side chain 22 24 , 35 , 36 . These findings underscore the importance of considering both affinity and transport efficiency when developing LAT1-targeted compounds.…”
Section: Discussionmentioning
confidence: 58%
“…This strategy utilizes LAT1 for enhanced delivery through the BBB to improve brain uptake. Gabapentin and l -DOPA have been shown to act as LAT1 substrates, though they possess relatively lower affinity compared to endogenous substrates like Phe 21 24 . In vivo studies revealed that a high protein diet or the infusion of large amounts of neutral amino acids before administering l -DOPA can reduce its transport to the brains of monkeys, implying that endogenous amino acids compete with l -DOPA for LAT1-mediated transport and high concentrations of these amino acids can reduce brain uptake of l -DOPA 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, a quantitative structure-activity relationship (QSAR) model was developed for designing potent binders of LAT1, which indicated that meta-substituted amide derivatives of phenylalanine (i.e., with an amide bond at the meta-position of the aromatic ring) have the highest ability to utilize LAT1 [ 105 ]. Subsequently, a detailed in vitro study was performed on the structural features affecting the transportability of LAT1-targeted phenylalanine-drug conjugates, providing further insight into suitable drug scaffolds for selective and efficient delivery via this strategy [ 106 ]. It should be noted that prodrugs designed to be substrates for LAT1 can also be substrates for other uptake transporters, such as monocarboxylate transporters 8 and 10 (MCT8/SLC16A2 and MCT10/SLC16A10, respectively), and organic anion transporter proteins (OATPs, SLCO/SLC21 family) [ 107 , 108 ].…”
Section: Targeting Transportersmentioning
confidence: 99%
“…Moreover, LAT1 is a very good candidate for the pro-drug approach, in which a drug molecule is linked to the physiological substrate of the transporter for facilitating membrane crossing. This approach is particularly interesting since LAT1 is physiologically expressed at the BBB, thus giving a further possibility to deliver a drug into the brain [ 20 ]. Therefore, LAT1 is an important target for research in drug discovery.…”
Section: Introductionmentioning
confidence: 99%